Food Food Nutrition Values Improvement Through Optimise of Potency Utilization of Banana Peels Flour of Plantain, Kepok, and Ambon - atikah proverawati; indah nuraeni; budi sustriawan (Jurnal Gizi dan Pangan Soedirman, 2019)
Banana of Kapok, Ambon and Plantain are widely used by the community, but their peels have not been utilized. Vitamins and minerals from banana peels are very high, so it need to increase the nutritional value of their food. This study aimed to analyze the physical and chemical characteristics of banana peel flour produced from three different banana varieties namely Plantain, Kapok and Ambon banana. This study used a factorial experimental with a completely randomized design (CRD) design, with different treatments of banana peel and soaking time varieties. Analysis of yield, color, water content, gel strength and stickiness, kamba density, solubility, water holding capacity, oil absorption, swelling power, moisture content, ash, protein, fat, carbohydrate, pectin levels, were carried out on banana peel flour. The results showed that the highest water content contained in the Ambon banana peels; the highest levels of ash, fat, protein and carbohydrate are in plantain peels; the highest crude fiber content are in Ambon banana peel, and the average pectin level of the three types of banana peels was 1.08%. Different types of banana peels and soaking time had a significant effect on water content, fiber content and banana flour pectin content.